Numerical analysis of threaded pin fins heat sink by natural convection / Muhammad Firdaus Hamidan ... [et al.] - Hamidan, Muhammad Firdaus; Bahsan, Rosnadiah; Tijani, Alhassan Salami; Zakaria, Irnie Azlin; Abdulrahman, Sajith Thottathil (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Heat sinks play a crucial role in thermal management by dissipating heat away from electronic devices and reducing the device’s performance. The heat sink with pin fins will enhance the rate of convective heat transfer and improve the cooling efficiency of electronic components by increasing the surface area. This study investigates the enhancement of heat transfer rate on square threaded pin fin heat sinks with or without perforation under natural convection. The fins were arranged in inline and staggered arrangement. Four different configurations were designed by using CATIA V5 and simulated by using CFD analysis with different power inputs at 5 W, 10 W and 15 W. The simulation results were validated with the experimental results from the previous study by comparing the heat transfer coefficient of the heat sink design by natural convection. The results show that the average heat transfer coefficient of square threaded pin fins with perforations in staggered arrangement is 7.365 W/m2.oC compared to the pin fins without perforations which is 7.168 W/m2.oC. Therefore, pin fin with perforation dissipates heat at the rate of 2.75% more than pin fin without perforation. In conclusion, the square threaded pin fins with perforations in staggered arrangement have higher heat transfer performance.